An Assessment of the National Institute of Standards and Technology Measurement and Standards Laboratories: Fiscal Year 2003 - National Research Council (The National Academies Press, 2003)

Materials Science and Technology: Challenges for the Chemical Sciences in the 21st Century - National Research Council
The report assesses the current state of chemistry and chemical engineering at the interface with materials science and identifies challenges for research. Recent advances are blurring the distinction between chemistry and materials science and are enabling the creation of new materials that, to date, have only been predicted by theory. These advances include a greater ability to construct materials from molecular components, to design materials for a desired function, to understand molecular \

Factors Affecting the Utilization of the International Space Station for Research in the Biological and Physical Sciences - National Research Council (The National Academies Press, 2003)

The National Earthquake Hazards Reduction Program at Twenty-Five Years: Accomplishments and Challenges – Summary of a Workshop, February 20, 2003, Washington, DC (The National Academies Press, 2003)

Future Challenges for the U.S. Geological Survey's Mineral Resources Program - National Research Council (The National Academies Press, 2003)
The committee assesses the USGS's responses to a 1996 program review, evaluates the minerals information team, and examines how the program's mission and vision might evolve to meet the nation's future needs over the next decade.

Materials and Society: From Research to Manufacturing: Report of a Workshop - National Research Council (The National Academies Press, 2003)

Exploration of the Seas: Interim Report - National Research Council (The National Academies Press, 2003)
Seventy percent of our blue planet is covered by oceans. Although progress has been made in understanding the role of oceans in climate change, locating energy reserves, revealing new life forms, and describing the flow of carbon through these systems, it may be time to catapult our understanding to new levels by undertaking an interdisciplinary, international, global ocean exploration program. The interim report outlines the committee's vision for a future international global ocean exploration program; this vision will be fully described, together with detailed recommendations for technological needs and capabilities, funding levels, and management structures to ensure a productive and successful ocean exploration program.

Use of Lightweight Materials in 21st Century Army Trucks - National Research Council (The National Academies Press, 2003)
In order to achieve the Army2019s envisioned Objective Force related to deployability, transportability, and mobility, the Committee on Lightweight Materials for the 21st Century Army Trucks was asked to identify research and technology development opportunities related to the introduction of new lightweight structural materials for light medium and heavy Army trucks.

Progress in Improving Project Management at the Department of Energy: 2002 Assessment - National Research Council (The National Academies Press, 2003)
In 1997, Congress, in the conference report, H.R. 105-271, to the FY1998 Energy and Water Development Appropriation Bill, directed the NRC to carry out a series of assessments of project management at the Department of Energy (DOE). This report, the 2002 Assessment, is the second in that series. It presents an examination of DOE's progress in improving program management over the past two years and offers recommendations regarding project management methodology and project oversight.

Information and Communications: Challenges for the Chemical Sciences in the 21st Century - National Research Council (The National Academies Press, 2003)
Since publication of the National Research Council (NRC) reports on chemistry in 1985 and chemical engineering in 1988,1,2 dramatic advances in information technology (IT) have totally changed these communities. During this period, the chemical enterprise and information technology have enjoyed both a remarkably productive and mutually supportive set of advances. These synergies sparked unprecedented growth in the capability and productivity of both fields including the definition of entirely new areas of the chemical enterprise. The chemical enterprise provided information technology with device fabrication processes, new materials, data, models, methods, and (most importantly) people. In turn, information technology provided chemical science and technology with truly remarkable and revolutionary resources for computations, communications, and data management. Indeed, computation has become the strong third component of the chemical science research and development effort, joining experiment and theory. Sustained mutual growth and interdependence of the chemical and information communities should take account of several unique aspects of the chemical sciences. These include extensive and complex databases that characterize the chemical disciplines; the importance of multiscale simulations that range from molecules to technological processes; the global economic impact of the chemical industry; and the industry's major influence on the nation's health, environment, security, and economic well-being. In planning the future of the chemical sciences and technology, it is crucial to recognize the benefits already derived from advances in information technology as well as to point the way to future benefits that will be derived.

Reducing the Time from Basic Research to Innovation in the Chemical Sciences: A Workshop Report to the Chemical Sciences Roundtable - National Research Council (The National Academies Press, 2003)
Innovation, the process by which fundamental research becomes a commercial product, is increasingly important in the chemical sciences and is changing the nature of research and development efforts in the United States. The workshop was held in response to requests to speed the R&D process and to rapidly evolve the patterns of interaction among industry, academe, and national laboratories. The report contains the authors' written version of the workshop presentations along with audience reaction.

Energy and Transportation: Challenges for the Chemical Sciences in the 21st Century - National Research Council (The National Academies Press, 2003)
This book, also based on a workshop, assesses the current state of chemistry and chemical engineering at the interface with novel and existing forms of energy and transportation systems. The book also identifies challenges for the chemical sciences in helping to meet the increased demand for more energy, and opportunities for research in energy technologies and in the development of transportation vehicles.

Improving the Regulation and Management of Low-Activity Radioactive Wastes: Interim Report on Current Regulations, Inventories, and Practices - National Research Council (The National Academies Press, 2003)
Low-activity radioactive wastes include a broad spectrum of materials for which a regulatory patchwork has evolved over almost 60 years. These wastes present less of a radiation hazard than either spent nuclear fuel or high-level radioactive waste. Low-activity wastes, however, may produce potential radiation exposure at well above background levels and if not properly controlled may represent a significant chronic (and, in some cases, an acute) hazard. For some low-activity wastes the present system of controls may be overly restrictive, but it may result in the neglect of others that pose an equal or higher risk. The purpose of this interim report is to provide an overview of current low-activity waste regulations and management practices. Improving the Regulation and Management of Low-Activity Radioactive Wastes: Interim Report on Current Regulations, Inventories, and Practices identifies gaps and inconsistencies that suggest areas for improvements. The final report will assess options for improving the current practices and provide recommendations.

Funding Smithsonian Scientific Research - National Research Council (The National Academies Press, 2003)
This report assesses whether the Smithsonian Institution should continue to receive direct federal appropriations for its scientific research programs or if this funding should be transferred to a peer-reviewed program open to all researchers in another agency. The report concludes that the National Museum of Natural History, the National Zoological Park, and the Smithsonian Center for Materials Research and Education in Suitland should remain exempt from having to compete for federal research dollars because they make unique contributions to the scientific and museum communities. Three other Smithsonian research programs should continue to receive federal funding since they are performing science of the highest quality and already compete for much of their government research money.

2001-2002 Assessment of the Army Research Laboratory - National Research Council (The National Academies Press, 2003)

Biographical Memoirs: Volume 82 - National Academy of Sciences (The National Academies Press, 2003)
Biographic Memoirs Volume 82 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

Leaving Earth: Space Stations, Rival Superpowers, and the Quest for Interplanetary Travel - Robert Zimmerman (The National Academies Press, 2003)
Charged with the ever-present potential for danger and occasionally punctuated by terrible moments of disaster, the history of space exploration has been keenly dramatic. The recent disaster of the Space Shuttle Columbia was a sad but certain reminder that space travel is an extraordinarily dangerous occupation. Oddly enough, it often takes a tragic accident to remind us that we still have a presence in space. In the decades between triumph and tragedy we tend to ignore the fact that there have been scores of space pioneers who have risked their lives to explore our solar system. Indeed, the International Space Station is sometimes referred to as 201cAlpha,201d a moniker that implies that it is our first real permanent presence in space. But this notion is frowned upon by the Russians 2013 and for good reason. Prior to the construction of the controversial International Space Station, a host of daring Russian cosmonauts, and a smaller number of intrepid American astronauts, were living in space for months, some of them for over a year. In this definitive account of man2019s quest to become citizens of the cosmos, noted space historian Robert Zimmerman reveals the great global gamesmanship between Russian and American political leaders that drove us to the stars. Beaten to the Moon by their Cold War enemies, the Russians were intent on being first to the planets. They believed that manned space stations held the greatest promise for reaching other worlds and worked feverishly to build a viable space station program 2013 one that would dwarf American efforts and allow the Russians to claim the vast territories of space as their own. Although unthinkable at the time, the ponderously bureaucratic Soviet Union actually managed to overtake the United States in the space station race. Leveraging their propaganda machine and tyrannical politics to launch a series of daring, dangerous, and scientifically brilliant space exploits, their efforts not only put them far ahead of NASA, they also helped to reshape their own society, transforming it from dictatorship to democracy. At the same time, the American space program at NASA was also evolving, but not necessarily for the better. In fact, the two programs were slowly but inexorably trading places. Drawing on his vast store of knowledge about space travel, as well as hundreds of interviews with cosmonauts, astronauts, and scientists, Zimmerman has superbly captured the excitement and suspense of our recent space-traveling past. For space and history enthusiasts alike, Leaving Earth describes a rich heritage of adventure, exploration, research, and discovery.

The Last Sorcerers: The Path from Alchemy to the Periodic Table - Richard Morris (The National Academies Press, 2003)
They started with four: earth, air, fire, and water. From these basics, they sought to understand the essential ingredients of the world. Those who could see further, those who understood that the four were just the beginning, were the last sorcerers 2013 and the world2019s first chemists. What we now call chemistry began in the fiery cauldrons of mystics and sorcerers seeking not to make a better world through science, but rather to make themselves richer through magic formulas and con games. But among these early magicians, frauds, and con artists were a few far-seeing 201calchemists201d who, through rigorous experimentation, transformed mysticism into science. By the 18th century the building blocks of nature, the elements of which all matter is composed, were on the verge of being discovery. Initially, it was not easy to determine whether a substance really was an element. Was water just water, plain and simple? Or could it be the sum of other (unknown and maybe unknowable) parts? And if water was made up of other substances, how could it be broken down into discreet, fundamental, and measurable components? Scientific historians generally credit the great 18th century French chemist Antoine Lavoisier with addressing these fundamental questions and ultimately modernizing the field of chemistry. Through his meticulous and precise work this chaotic new field of scientific inquiry was given order. Exacting by nature, Lavoisier painstakingly set about performing experiments that would provide lasting and verifiable proofs of various chemical theories. Unfortunately, the outspoken Lavoisier eventually lost his head in the Terror, but others would follow his lead, carefully examining, measuring, and recording their findings. As the field slowly progressed, another pioneer was to emerged almost 100 years later. Dimitri Mendeleev, an eccentric genius who cut his flowing hair and beard but once a year, sought to answer the most pressing questions that remained to chemists: Why did some elements have properties that resembled those of others? Were there certain natural groups of elements? And, if so, how many, and what elements fit into them? It was Mendeleev who finally addressed all these issues when he constructed the first Periodic Table in the late 1800s. But between and after Lavoisier and Mendeleev were a host of other colorful, brilliant scientists who made their mark on the field of chemistry. Depicting the lively careers of these scientists and their contributions while carefully deconstructing the history and the science, author Richard Morris skillfully brings it all to life. Hailed by Kirkus Reviews as a 201cclear and lively writer with a penchant for down-to-earth examples201d Morris2019s gift for explanation 2013 and pure entertainment 2013 is abundantly obvious. Taking a cue from the great chemists themselves, Morris has brewed up a potent combination of the alluringly obscure and the historically momentous, spiked with just the right dose of quirky and ribald detail to deliver a magical brew of history, science, and personalities.

Exploration of the Seas: Voyage into the Unknown - National Research Council (The National Academies Press, 2003)
In the summer of 1803, Thomas Jefferson sent Meriwether Lewis and William Clark on a journey to establish an American presence in a land of unqualified natural resources and riches. Is it fitting that, on the 200th anniversary of that expedition, the United States, together with international partners, should embark on another journey of exploration in a vastly more extensive region of remarkable potential for discovery. Although the oceans cover more than 70 percent of our planet's surface, much of the ocean has been investigated in only a cursory sense, and many areas have not been investigated at all. Exploration of the Seas assesses the feasibility and potential value of implementing a major, coordinated, international program of ocean exploration and discovery. The study committee surveys national and international ocean programs and strategies for cooperation between governments, institutions, and ocean scientists and explorers, identifying strengths, weaknesses, and gaps in these activities. Based primarily on existing documents, the committee summarizes priority areas for ocean research and exploration and examines existing plans for advancing ocean exploration and knowledge.

Assessment of Directions in Microgravity and Physical Sciences Research at NASA - National Research Council (The National Academies Press, 2003)
For thirty years the NASA microgravity program has used space as a tool to study fundamental flow phenomena that are important to fields ranging from combustion science to biotechnology. This book assesses the past impact and current status of microgravity research programs in combustion, fluid dynamics, fundamental physics, and materials science and gives recommendations for promising topics of future research in each discipline. Guidance is given for setting priorities across disciplines by assessing each recommended topic in terms of the probability of its success and the magnitude of its potential impact on scientific knowledge and understanding; terrestrial applications and industry technology needs; and NASA technology needs. At NASA2019s request, the book also contains an examination of emerging research fields such as nanotechnology and biophysics, and makes recommendations regarding topics that might be suitable for integration into NASA2019s microgravity program.